2015
DOI: 10.1017/thg.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes in theIGF1RGene in Birth Weight Discordant Adult Monozygotic Twins

Abstract: Low birth weight (LBW) can have an impact on health outcomes in later life, especially in relation to predisposition to metabolic disease. Several studies suggest that LBW resulting from restricted intrauterine growth leaves a footprint on DNA methylation in utero, and this influence likely persists into adulthood. To investigate this further, we performed epigenome-wide association analyses of blood DNA methylation using Infinium HumanMethylation450 BeadChip profiles in 71 adult monozygotic (MZ) twin pairs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 95 publications
(140 reference statements)
0
16
2
Order By: Relevance
“…These epigenetic differences may account for phenotypic discordance in MZ twins. Multiple studies have explored the epigenetic changes in twins discordant for a range of congenital diseases, including autism spectrum disorder (Nguyen et al, 2010 ; Wong et al, 2014 ), birth weight (Souren et al, 2013 ; Tsai et al, 2015 ), congenital renal agenesis (Jin et al, 2014 ), and congenital cataracts (Wei et al, 2015 ). Recently, epigenetic aberrations have been sought in CHDs (Serra-Juhé et al, 2015 ; Vecoli et al, 2015 ) but not in CHD-discordant twins.…”
Section: Discussionmentioning
confidence: 99%
“…These epigenetic differences may account for phenotypic discordance in MZ twins. Multiple studies have explored the epigenetic changes in twins discordant for a range of congenital diseases, including autism spectrum disorder (Nguyen et al, 2010 ; Wong et al, 2014 ), birth weight (Souren et al, 2013 ; Tsai et al, 2015 ), congenital renal agenesis (Jin et al, 2014 ), and congenital cataracts (Wei et al, 2015 ). Recently, epigenetic aberrations have been sought in CHDs (Serra-Juhé et al, 2015 ; Vecoli et al, 2015 ) but not in CHD-discordant twins.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from whole blood, bisulfite converted and subsequently analyzed using the Infinium 450K kit as previously described [ 50 ]. The beta mixture quantile dilation (BMIQ) method was performed to correct for technical variation [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…One of the most stable epigenetic processes is DNA methylation, or the addition of a CH 3 methyl group to cytosine, typically in the context of cytosine paired sequentially to a guanine nucleotide, separated by a phosphate group (CpG). DNA methylation is known to play a role in gene expression and cell differentiation, and differential DNA methylation has been linked to multiple human complex traits and disease phenotypes . Studies performed using bone samples have identified epigenetic alterations that influence bone cell function .…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is known to play a role in gene expression and cell differentiation, (7,8) and differential DNA methylation has been linked to multiple human complex traits and disease phenotypes. (5,(9)(10)(11)(12) Studies performed using bone samples have identified epigenetic alterations that influence bone cell function. (13,14) We studied epigenetic variation in whole blood, as a proxy for difficult-to-acquire samples such as bone, in relation to BMD because epigenetic markers are often stable across multiple tissues, and immune cells within blood are known to influence bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%